Prévoir pour filmer la parole - Myriam Mayer (Catalonia)
In this article, we propose to analyse the words filmed in the documentary En construcción (José Luis Guerin, 2001), to study the complex links woven between the seen and the heard, between the visible and the invisible. We study precisely the various functions given to Antonio's speech when he first appeared in the film and reflect on the relationships established between the voice of power and the power of the voice. We therefore come to consider the discourse of the film, the one that the filmmaker elaborates through its editing.